Miniaturized Chipless RFID Tags Based on Periodically Loaded Microstrip Structure - Added, M.; Rabaani, K.; Chabaan, S.; Boulejfen, N. (Engineering, Technology & Applied Science Research, 2019)
A compact chipless radio frequency identification (RFID) tag-based on slow-wave technology is introduced in this paper. The tag consists of a resonant circuit based on open stub resonators periodically loaded by shunt stubs allowing a coding capacity of 9 bits and operating in a frequency range from 2 to 4GHz. The receiving and transmitting antennas of the tag are particularly designed to minimize the tag size as much as possible. The proposed tag presents a robust bit pattern with a compact and fully printable structure using FR4 substrate for a low-cost tag.